2012
DOI: 10.1016/j.jcmg.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Trabeculae and Papillary Muscles With Clinical and Cardiac Characteristics and Impact on CMR Measures of LV Anatomy and Function

Abstract: Objective We sought to assess the relationship of left ventricular (LV) trabeculae and papillary muscles (TPM) with clinical characteristics in a community-based, free living adult cohort and to determine the effect of TPM on quantitative measures of LV volume, mass and ejection fraction (EF). Background Hypertrabeculation has been associated with adverse cardiovascular events, but the distribution and clinical correlates of the volume and mass of the TPM in a normal left ventricle have not been well charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
68
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 19 publications
(26 reference statements)
11
68
1
Order By: Relevance
“…Our data regarding the sum of papillary muscle and trabecular mass in the left ventricle was consistent with large population based literature data in all observers [10].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data regarding the sum of papillary muscle and trabecular mass in the left ventricle was consistent with large population based literature data in all observers [10].…”
Section: Discussionsupporting
confidence: 90%
“…It is difficult to compare literature data because of the diverse evaluation of TPM volumes. The majority of prior studies presented data that was either papillary muscle or trabecular mass measurement in isolation [5][6][7][8]; few studies 1 3 are available which reported the sum of papillary and trabecular mass [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26] Three-dimensional TTE was not used in this study, though does have some advantages over 2D-TTE and could be compared to CMR in future studies. Other limitations of this study are the modest study size and small number of primary endpoints.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In particular, the inclusion or exclusion of trabecular myocardium in global LV mass assessment has not been standardized. 21 In the present study, 1 the investigators manually traced the epiand endocardial contours of the LV-excluding trabeculations-to determine myocardial volumes (myocardial volume = epicardial volume -endocardial volume). By multiplying myocardial volumes with the cardiac density (q = 1.05 g/mL), they obtained the LV mass.…”
mentioning
confidence: 99%